Theoretical Substantiation of the Support Model for Master’s Degree Students’ Self-Determination during Teaching Practice - E. V. Neumoeva-Kolchedantseva (Образование и наука)
Introduction. In the conditions of complexity, uncertainty, and diversity of contemporary Russian reality, the task of personal self-determination for the future teacher, understood as a mechanism of self-regulation, becomes a priority. In this regard, it is appropriate to consider teaching practice not only in the context of professional self-determination, but including personal selfdetermination. The “activity-based” interpretation of personal self-determination provides the prospects for finding an integrative pedagogical mechanism, which mediates the process of future teachers’ personal self-determination. The aim of the present research is the conceptualisation of ideas about pedagogical support as a mechanism and form of mediating personal selfdetermination, theoretical substantiation of the model for pedagogical support of students’ personal self-determination during the period of teaching practice. Methodology and research methods. To achieve the goal of the research, a reliable theoretical and methodological base has been defined: cultural-historical theory, psychological theory of activity, subject-activity approach, modern interpretation of the existential approach in psychology, environmental approach, and hermeneutic approach in pedagogy. The following methods of theoretical level are used: analysis of the main tendencies of modern pedagogical education development; analysis of basic theories and approaches; conceptualisation of pedagogical support ideas; hypothesis, modelling, extrapolation; generalization of research results. The materials of the research are: the sources of scientific information recognised in the scientific community (47 sources), included in the RSCI citation base, in the international citation systems Web of Science, Web of Science (RSCI), Scopus; well-known models of psychological and pedagogical support of a person in the educational process; local experience of testing the author’s model for supporting students’ personal self-determination during the period of teaching practice. Results. A developed theoretical model for supporting students’ personal self-determination during the period of teaching practice includes: design of the individual trajectory for development as the main means of support; justification of the interaction between tutors and students as the main mode of pedagogical support; disclosure of meaningful dominants of support at the main stages of personal interaction with the social and educational environment; general characterisation of the proposed methods and means of pedagogical support. The strategy of pedagogical support is proposed, taking into account the essential properties of personal self-determination (an activity of externally and internally mediated process) and the objective possibilities of teaching practice as a “space of self-determination”, which consists in ensuring the movement of the individual from external to internal, from unconscious to conscious, from passive to intentional, from spontaneous to a controlled process of selfdetermination. Scientific novelty. For the first time, pedagogical support is justified as a mechanism for mediating the personal self-determination of a future teacher. The model of pedagogical support as a mediating activity of a teacher is theoretically substantiated. The novelty of the model lies in the restructuring of the relations of its main elements: the support stages are isomorphic to the stages of selfdetermination; the “prolonged” means of support is an individual development path that integrates other means and methods. Special attention is focused on the role of the tutor’s personality and his or her interaction with students. Practical significance. The model of pedagogical support is presented as the basis for the prospective design and practical implementation of the maintenance procedure, designing and testing its methods and means, comprehending and “enriching” its content. Thus, the demonstrated model is designed to contribute to the formation of pedagogical support for the personal self-determination of future teachers as a real and in-demand educational practice in the current conditions of educational practice.